Analisis Keterampilan Berbicara Siswa Kelas IV pada Mata Pelajaran Bahasa Indonesia di SDN Rawa Buaya 07 - Maryanti, Dwi Setyo; Nurfadhillah, Septy; Arwen, Desri (Lembaga Yasin AlSys, 2022)
This study aims to answer the results of the analysis and describe the speaking skills of fourth grade students in Indonesian subjects at SDN Rawa Buaya 07. The approach method used in this research is descriptive qualitative by taking data at SDN Rawa Buaya 07 with the research subjects being teachers and class students. IV. Data was collected by observation, interviews, oral tests and documentation. Data analysis was carried out through three stages of implementation, namely data reduction, data presentation and drawing conclusions. Checking the validity of the data used includes triangulation of sources, triangulation of data collection techniques, triangulation of time and guarantor of validity. The results obtained indicate that the speaking skills of fourth grade students in Indonesian subjects at SDN Rawa Buaya 07 are in the